Auf der Suche nach dem Gedächtnis - Der Hirnforscher Eric Kandel - Seeger, Petra (Germany : FilmForm Cologne, 2008)
“In Search of Memory” parallels the life story and groundbreaking work of one of the most important neuroscientists of the 20th century, Nobel Prize-winner Eric Kandel. The spry and quick-witted 79-year-old Kandel leaps off the screen as a magnetic personality and force of life. Born in 1929 Vienna to a lower-middle class Jewish family, he emigrated to the United States to escape Nazi persecution before devoting his life's work to understanding the brain's role in recording and preserving memory. Kandel retraces his traumatic childhood and strong ties to Judaism, and its influence in his pioneering research to understand "the glue that binds our mental life together." Dramatic recreations of Kandel's formative years along with archival footage make for an unforgettable biography.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films